Questão fundiária: posse tradicional versus propriedade da terra entre Brasil e Cabo Verde - Carolina dos Anjos de Borba (Ciências Sociais Unisinos)
This paper intends to analyze the social processes which enabled the ascension of slaves descendants as land owners in post-colonial contexts. The debate raised intends to discuss the relations that produce truth discourses, in which the old leasers (Cape Verde) and quilombolas (Brazil) do not easily constitute themselves as land owners. The state of emergency theories understand these phenomena of political oscillation as a peculiar way of safeguarding the public security in an arbitrary paradigm of government. Thus, we will present claims that show land insecurity in these two countries in the complex framework of the state of the emergency that mix ethnic and political elements. We will present two rural universes: São Salvador do Mundo (Cape Verde) and Canguçu (Brazil). The first one faced hard territorial struggles between morgados and leasers, undergoing the agrarian reform project and currently is under the owning of small proprietaries. The second one experienced various historical changes related to the south land issue, besides concentrating, in its territorial space, a large number of slave workers. Additionally, the two localities offer dense ethnographic materials to work the theoretical issue of "land-security".